Remittances and Labor Supply in the Northern Triangle - Sousa, Liliana D.; Garcia-Suaza, Andres (World Bank, Washington, DC, 2018)
Through substitution and income effects, remittances can alter an individual's allocation of time between market activities and household production, decreasing labor supply. This paper uses propensity score matching and household surveys for 2006 and 2014 to estimate the impact of remittances on labor supply in the three countries of the Northern Triangle (El Salvador, Guatemala, and Honduras). The results show that remittances are associated with a reduction in labor force participation, particularly among women. This effect is largest for Salvadoran women (13 percentage points). A sensitivity analysis finds that the negative effect on labor force participation rates of men in El Salvador and Guatemala and women in El Salvador is robust to potential selection bias. Receiving remittances is also associated with a lower likelihood of young adults being in school or at work, with this effect being robust to selection bias for young men in Guatemala. At the same time, the evidence suggests that remittances may be supporting small enterprises and self-employment in El Salvador and Guatemala. The analysis does not find robust evidence of remittances affecting the labor supply in Honduras in 2014.